(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Elfrida, Tarigan NS, Suwardi AB. 2021. Ethnobotanical study of medicinal plants used by community in Jambur Labu Village, East Aceh, Indonesia. Biodiversitas 22: 2893-2900. Jambur Labu is a village in East Aceh that is home to various ethnic groups. The community in the village has used various plant species as a traditional medicine to treat diseases and disorders. The aim of this study was to investigate the medicinal plants used by the community in the Jambur Labu Village, Birem Bayeun Sub-district, East Aceh, Indonesia. This study was based on field surveys, plant collection, and interviews with the local people. Interviews were performed with 30 informants selected using the Snowball Sampling technique. A total of 107 medicinal plant species, belonging to 87 families, were documented to be used by the local community in Jambur Labu Village. Leaves were the most used plant part (38%), followed by fruit (22%), whole plant (9%), rhizome (8%), roots (7%), flowers and bark (4% each), sap (3%), stem and tuber (2% each), and seeds (1%) and the main mode of preparations are decoction (39%). Breynia androgyna (L.) Chakrab.dan N.P.Balakr., Moringa oleifera Lam, Jatropha multifida L., Zingiber montanum (J.Koenig) Link ex A.Dietr., Zingiber officinale Roscoe., and Tagetes erecta L. had the highest UV value (0.96), indicating the high importance of such species for the community. The high informant consensus factor (ICF=0.978) was assigned to the diseases of the blood and blood-forming organs and certain disorders involving the immune mechanism (DBF) category. The results of this study can enrich the existing study of medicinal uses of plant by communities, in this context is the use by a community in Aceh.